2014
DOI: 10.1523/jneurosci.3475-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

A Lipid Gate for the Peripheral Control of Pain

Abstract: Cells in injured and inflamed tissues produce a number of proalgesic lipid-derived mediators, which excite nociceptive neurons by activating selective G-protein-coupled receptors or ligand-gated ion channels. Recent work has shown that these proalgesic factors are counteracted by a distinct group of lipid molecules that lower nociceptor excitability and attenuate nociception in peripheral tissues. Analgesic lipid mediators include endogenous agonists of cannabinoid receptors (endocannabinoids), lipid-amide ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 83 publications
0
57
0
1
Order By: Relevance
“…Terashvili, et al, 2008), as well as the specific analgesia-relevant P450 isoforms/genes. New kinds of pain relievers are being developed based upon the analgesic activity of lipid epoxides and congeners (Brostram and Falck, 2011;Piomelli, et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Terashvili, et al, 2008), as well as the specific analgesia-relevant P450 isoforms/genes. New kinds of pain relievers are being developed based upon the analgesic activity of lipid epoxides and congeners (Brostram and Falck, 2011;Piomelli, et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…[1,[2][3][4][5][6][7][8][9][10][11][12][13][14] C]ethanolamine HCl was from Moravek Biochemicals (Brea, CA). Horseradish peroxidaselinked anti-mouse and anti-rabbit IgGs were from GE Healthcare (Piscataway, NJ).…”
Section: 2-[1′-mentioning
confidence: 99%
“…It has also been suggested that 2-AG controls cellular differentiation in skeletal muscle [13]. Furthermore, ECs and endogenous PPAR-α activating NAEs are proposed to be key players as regulators of nociceptive information transmitting from peripheral sites of injury and inflammation to CNS [14,15].…”
Section: Introductionmentioning
confidence: 99%